THE MONGOLS IN REGION AND STRUGGLE AGAINST THEIR OPPRESSION - Teshaboyeva Nafisa Zubaydulla qizi; Aliyeva Saida Aziz qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation This paper examines the historical presence of the Mongols in various regions and the resistance movements that arose against their oppression. It explores the causes of Mongol expansion, the impact on local societies, and the strategies employed by the oppressed communities to protect their autonomy and culture. Through a historical and analytical approach, the study highlights the significance of resistance movements in shaping regional histories and maintaining cultural identity. The research draws on primary historical records and modern scholarly analyses to provide a comprehensive understanding of the Mongol invasions and the corresponding struggles.